PERAN KOMUNITAS KRISTEN SEBAGAI JEMBATAN KASIH DI TENGAH PENDERITAAN BANGSA INDONESIA - Mathias Adon (Vox Dei: Jurnal Teologi dan Pastoral, 2021)
This research has the aim of unraveling the reality of suffering that is hitting the world due to the Covid-19 Pandemic from the point of view of Christian spirituality. In Indonesia, this emergency is exacerbated by religious radicalism and various natural disasters. In this situation, human existence seems to be at the limit of pilgrimage. Therefore, the presence of fellow Christians, especially Christians, is expected to be a bridge of God's love amid the suffering of others. Christians can start by living in brotherly love in the community. Because in the Christian community people are more sensitive to hear the suffering of others. In other words, by living in a community, Christians can help those affected out of the trap of the horrors of suffering. Therefore, Unity in community enables Christians to heal the wounded and bring the dead to life. The novelty of this paper lies in the role of the Christian community as a forum and means for Christians to manifest God's love in the suffering of the Indonesian nation. Because without togetherness in community, Christians will lose their identity, and love will become a broken branch. To describe this thesis, this research uses a phenomenological approach whose truth is not based on deductive principles, but concrete human experiences.